Basal cell carcinoma, squamous cell carcinoma and melanoma of the head and face. Issue 1 (December 2016) - Feller, L.; Khammissa, R.; Kramer, B.; Altini, M.; Lemmer, J.
Abstract Ultraviolet light (UV) is an important risk factor for cutaneous basal cell carcinoma, cutaneous squamous cell carcinoma and cutaneous melanoma of the skin. These cancers most commonly affect persons with fair skin and blue eyes who sunburn rather than suntan. However, each of these cancers appears to be associated with a different pattern of UV exposure and to be mediated by different intracellular molecular pathways. Some melanocortin 1 receptor (MC1R) gene variants play a direct role in the pathogenesis of cutaneous basal cell carcinoma, cutaneous squamous cell carcinoma and cutaneous melanoma apart from their role in determining a cancer-prone pigmentory phenotype (fair skin, red hair, blue eyes) through their interactions with other genes regulating immuno-inflammatory responses, DNA repair or apoptosis. In this short review we focus on the aetiological role of UV in cutaneous basal cell carcinoma, cutaneous squamous cell carcinoma and cutaneous melanoma of the skin, and on some associated biopathological events.